Pengaruh Penerapan Total Quality Management Terhadap Kinerja Karyawan - Angela M. Tae; Rahmat Laan; Muhran Muhran (Jurnal Manajemen, 2019)
This study aims to determine the effect of Total Quality Management (TQM)on employee performance. The research sample of 23 people. Determinationof the sample using the saturated sample technique. The main instrument ofdata collection is a questionnaire. Data were analyzed using multipleregression techniques. The results showed that aspects of customer focus,education and training, employee involvement and empowerment, andcontinuous system improvement, partially had a significant effect onemployee performance. The aspects of customer focus, education andtraining, employee involvement and empowerment, and continuous systemimprovement also simultaneously have a significant effect on employeeperformance.